The impact of social and cultural factors on the consumption of western fast food among Chinese children. (8th January 2015) - Song, Chunyan; Goto, Keiko; Hu, Min; Wolff, Cindy
Abstract : This study examines the impact of social and cultural factors on the consumption of western fast food among Chinese children in China. A total of 500 caregivers of k-2 children from two Chinese cities participated in a cross-sectional survey study in 2011. The study demonstrates that consumption of western fast food among Chinese children can be largely attributed to three factors: accessibility of fast food, mother's education level, and caregiver's ideology on western food. Urban children are more likely to consume western fast food than their rural and suburban counterparts. When mothers have some college education, children have a much higher likelihood of consuming western fast food than children with less educated mothers. Additionally, when caregivers view western food as a good and necessary cultural exposure, children are more likely to consume western fast food. The complexity of social and cultural capital measures in the context of child feeding practices and community development is discussed.